2005
DOI: 10.2460/javma.2005.227.1091
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of arthroscopic and radiographic abnormalities in the hip joints of juvenile dogs with hip dysplasia

Abstract: Results suggest that radiography is not a sensitive method for identifying moderate cartilage lesions in juvenile dogs with hip dysplasia. If moderate cartilage lesions are an important prognostic indicator for the success of triple pelvic osteotomy, then methods other than radiography should be used to detect these lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 10 publications
0
31
0
2
Order By: Relevance
“…[4][5][6] Successful long-term treatment of HD with DPO has been demonstrated 12 ; however, poor candidate selection may lead to treatment failure with progression of hip arthritis and degenerative joint disease in treated dogs. 8 Despite the utility of the DI for predicting future development of coxofemoral joint disease, it is not clear that the magnitude of the DI would be an accurate predictor of the current level of degenerative changes in any individual hip joint. Arthroscopy is considered the gold standard for assessing articular cartilage, synovium, and intra-articular ligaments in many joints in the dog and in other species 8,10,13 but is not routinely used to assess the coxofemoral joint in dogs prior to DPO surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[4][5][6] Successful long-term treatment of HD with DPO has been demonstrated 12 ; however, poor candidate selection may lead to treatment failure with progression of hip arthritis and degenerative joint disease in treated dogs. 8 Despite the utility of the DI for predicting future development of coxofemoral joint disease, it is not clear that the magnitude of the DI would be an accurate predictor of the current level of degenerative changes in any individual hip joint. Arthroscopy is considered the gold standard for assessing articular cartilage, synovium, and intra-articular ligaments in many joints in the dog and in other species 8,10,13 but is not routinely used to assess the coxofemoral joint in dogs prior to DPO surgery.…”
Section: Discussionmentioning
confidence: 99%
“…8 Despite the utility of the DI for predicting future development of coxofemoral joint disease, it is not clear that the magnitude of the DI would be an accurate predictor of the current level of degenerative changes in any individual hip joint. Arthroscopy is considered the gold standard for assessing articular cartilage, synovium, and intra-articular ligaments in many joints in the dog and in other species 8,10,13 but is not routinely used to assess the coxofemoral joint in dogs prior to DPO surgery. The study reported here provides evidence that the results of arthroscopic assessment of coxofemoral joint cartilage and support structure (DAR, ligament of insertion of the femoral head, and labrum) wear do not correlate with the degree of coxofemoral joint laxity as measured by the DI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been reported to be a superior method than radiography for the identification of cartilage lesions in young dogs (Holsworth et al . ).…”
Section: Introductionmentioning
confidence: 97%